Profiles Junior high School West Java in Education Learning Environment - NFN Nahadi; Wiwi Siswaningsih; Farida Sarimaya (Intelektual Pustaka Media Utama, 2014)
Descriptive studies have been conducted on the existing junior high profile in West Java on Education Learning Environment. The study was conducted by purposive sampling and descriptive done to get an idea about the profile of SMP in West Java implementation of the learning environment. in junior high school in West Java. Research conducted by distributing questionnaires, and observations based on the indicators developed. Based on this research, it is known that, PLH learning in junior high school in West Java has been in force since 2007 after the enactment of the Governor of West Java on environmental education for junior high school students in West Java. Learning that lasts generally implemented in conventional teacher, and it is without any innovations. It has made learning the essential condition runs well, but has not lasted optimally.